2001
DOI: 10.1590/s0036-36342001000100006
|View full text |Cite
|
Sign up to set email alerts
|

La práctica de la medicina tradicional en América Latina y el Caribe: el dilema entre regulación y tolerancia

Abstract: This paper characterizes the current stage of traditional medicine in nine countries of Latin America and the Caribbean. Material and methods. This qualitative study was conducted between March and December 1998. Data were collected on the components of traditional health systems in countries of Latin America and the Caribbean, by means of a network of individuals and institutions from different countries that acted as expert informants from different specialty areas. Results. Findings from the analysis of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 20 publications
0
18
0
10
Order By: Relevance
“…O Brasil difere de outros países na oferta de práticas integrativas e complementares, pois predominam as práticas corporais, principalmente nos serviços públicos, o que não coincide com os estudos realizados em países da América Latina 3,20,25 . No SUS, as atividades físicas fazem parte das estratégias para a promoção da saúde, e são justificadas pelos estudos internacionais 26 que mostram sua efetividade para alguns fatores de risco à saúde.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O Brasil difere de outros países na oferta de práticas integrativas e complementares, pois predominam as práticas corporais, principalmente nos serviços públicos, o que não coincide com os estudos realizados em países da América Latina 3,20,25 . No SUS, as atividades físicas fazem parte das estratégias para a promoção da saúde, e são justificadas pelos estudos internacionais 26 que mostram sua efetividade para alguns fatores de risco à saúde.…”
Section: Discussionunclassified
“…A política de medicamentos fitoterápicos no SUS é ainda polêmica e tem sido alvo de críticas, principalmente porque há poucos estudos de efetividade, mesmo com os vários incentivos da OMS 1,2 e do Ministério da Saúde do Brasil 3 . Esse aspecto pode mostrar, da mesma forma que em outros países da América Latina 25 , que a institucionalização é insuficiente para o seu desenvolvimento.…”
Section: Discussionunclassified
“…A study that was performed in nine Latin American and Caribbean countries demonstrated that the majority had no legislation supporting these practices, although they were quite widespread and accepted by the societies in such countries. 13 This study showed that a chosen group of actors acted as the main players in the investigated policy and thus concludes that policy formation and enactment in this instance had an elitist nature because the policies were carried out by fi rst-rank politicians (Figure 2). According to Thomas & Gilson,20 when a diverse set of actors contribute to the process, including health care professionals, important changes can be made to the health system.…”
Section: "(…) the Acupuncture Society Is Fully Closed And Does Not Almentioning
confidence: 71%
“…Este concepto viene siendo reconocido por organizaciones internacionales como la Organización Mundial de la Salud (OMS) y la propia Organización Panamericana de la Salud (OPS) de quienes han emanado intentos de apoyo y promoción de políticas dirigidas a ensayar formas distintas de articulación de esta medicina con los sistemas oiciales de salud, enfocadas primordialmente en la atención primaria a la salud (15) .…”
Section: Medicina Complementaria Y Dilemas éTicos En Investigaciónunclassified